Book Review: Essays Into Vietnamese Pasts. Edited by K. W. Taylor and John K. Whitmore. Ithaca, N.Y.: Southeast Asia Program, Cornell University Press, 1995. 288 pp. $20.00 (paper). - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911800029971/resource/name/firstPage-S0021911800029971a.jpg
Keywords: book.review; dept.his

Book Review: Sexual Attraction and Childhood Association: A Chinese Brief for Edward Westermarck. By Arthur P. Wolf. Stanford, Calif.: Stanford University Press, 1995. xxiii, 561 pp. $65.00. - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS002191180002934X/resource/name/firstPage-S002191180002934Xa.jpg
Keywords: book.review; dept.his

Book Review: Chinese Acupuncture [l'Acuponcture Chinoise: La Tradition chinoise classifiée, precisée]. (Paris: Maloine, 1972). By George Soulié de Morant. Translated by Lawrence Grinnell, Claudy Jeanmougin and Maurice Leveque. Edited by Paul Zmiewski. Brookline, Mass.: Paradigm Publications, 1994. xxxii, 896 pp. $125.00. - Thompson, C. Michele (The Journal of Asian Studies, 1996)
//static.cambridge.org/content/id/urn%3Acambridge.org%3Aid%3Aarticle%3AS0021911800040171/resource/name/firstPage-S0021911800040171a.jpg
Keywords: book.review; dept.his

Vietnam - Thompson, C Michele (Acquiring Cross-Cultural Competence: Four Stages for Students of French vol I., 1998)
Keywords: dept.his

Book Review: Chinese in the Post-Civil War South; a People Without a History - Thompson, C Michele (The Southern Historian, 1985)
Keywords: book.review; dept.his